Shifting feed delivery time: effects on feeding behavior, milk production, and blood biomarkers in late-lactating dairy cows - Cattaneo, Luca; Passamonti, Matilde Maria; Piccioli-Cappelli, Fiorenzo; Trevisi, Erminio (Frontiers in Animal Science, 2024)
Improving the synchronization between the pattern of milk synthesis and nutrient availability throughout the day could enhance production efficiency. In this study, we evaluated the effects of changing feed delivery time on milk production, feeding behavior, and the daily rhythms of blood biomarkers. Eight multiparous Holstein cows housed in a tie-stall barn with controlled environmental conditions were enrolled in a crossover experimental design with 3 periods of 14 days and 3 treatments each. Cows were milked twice daily (0530 and 1730 h) and were individually fed with 2 equal meals of forages and 8 equal meals of concentrate during the day. Forage meals were provided at 12-hour intervals either: (i) 5 h before each milking (0030 and 1230 h; BM), (ii) at the end of each milking (0530 and 1730 h; ME), (iii) or 2 h after (0730 and 1930 h; AM). Feed intake and feeding behavior were monitored, and milk production and composition were measured. Blood samples were collected every 4 days at 0700 h and, during the last day of each period, 15 times daily to determine metabolic profile, hormones, and their daily rhythmicity by the cosinor analysis. ME cows produced more milk and ate more feed than the other groups, without any difference observed in feeding behavior when expressed relative to the first meal. There were no differences in milk component contents, but fat, protein, and lactose yields were greater in ME than in AM and BM. In samples collected at 0700 h, ME had reduced plasma Ca, Mg, and K, and increased Na. AM had worse liver function and increased inflammation, as suggested by the greater blood γ-glutamyl transferase, alkaline phosphatase, bilirubin, globulin, and ceruloplasmin. The patterns of metabolic biomarkers had limited variations when expressed relative to the first forage meal. ME cows had a lower nadir for glycemia, paired with more marked peaks for insulin and BHB. Nevertheless, the daily rhythms of these biomarkers were remarkably different. Under our conditions, feeding cows immediately after milking resulted in the greatest daily milk yield, also highlighting the importance of considering the sampling time when interpreting metabolic profiles.